Peran Pemerintah Dalam Menangani Masuknya Alfamart Dan Indomaret Di Tanjung Pinang - Indah Utami; mellyana candra; Wan Maulidia (Lembaga Pengembangan Kinerja Dosen, 2024)
Tanjung Pinang is the capital of the Riau Islands which has so many UMKM in the area that need to be fostered and developed so that all the businesses they own can become the focus of the community. Planning for the entry of Alfamart and Indomaret requires further study. Is it really necessary and very important for its existence in Tanjungpinang? So it is interesting in this research how intensive the government is in achieving the goal of entering this company and how urgent it is in the Tanjungpinang economy. Because in reality so many supermarkets in Tanjung Pinang will suffer losses and are far from profitable. So the role of government in providing policies must be more precise. This research uses a descriptive quantitative method, by collecting existing data related to existing problems using literature studies, interviews and other references. The aim of this research is to find out why the entry of Alfamart and Indomaret in Tanjung Pinang was rejected and what the future urgency of this is. And with research, it will form and add references to other students which will give rise to relevant answers